Іле Алатауы бойынша тат саңырауқұлақтарының аз зерттелген түрлері: биологиясы, табылған жері және иелік өсімдіктері (Experimental biology, 2018)
Information about rust fungi of Zailiyskiy Alatau is not sufficient and is considerably outdated (especially taxonomy of species). Therefore, the aim of the work was to identify little-known species of rust fungi on the territory of the Ile-Alatau national Park, a description of their biology and locations, the establishment of a circle of host plants. The scientific and practical significance of the work is to obtain data on the new locations of little-known rust fungi, which are of great importance in the development and reproduction of host plants. The material for the article was the authors ' own collections from the research area. Preparation of preparations was carried out according to the standard technique. The samples were studied and photographed using a photomicroscope Polyvar with interference optics Nomarsky.Given the description, location, host range and photomicrographs of selected structures of 7 little-known species of rust fungi the Trans-Ili Alatau: Pucciniastrum pyrolae on Pyrola rotundifolia and Moneses uniflora; P. goodyerae on Goodyera repens; Hyalopsora polypodii on Cystopteris fragilis; Puccinia atragenicola on Atragene sibirica; Micropuccinia retecta on Anemonastrum protractum; Puccinia thesii on Thesium alatavicum; P. mougeotii on Thesium alatavicum. Of the 7 little-known species described, only Puccinia atragenicola, Micropuccinia retecta and Puccinia mougeotii are rare. P. mougeotii is a rare species in other regions. Pucciniastrum pyrolae and P. goodyerae are quite common, but due to the small size of the host plants are not always seen by researchers, especially since the lesions are located on the lower side of the leaf blade. As for the Hyalopsora polypodii on Cystopteris fragilis, in connection with the habitats of the host plant (under stones), the fungus is rarely collected during mycological survey. The value of the study and practical value lies in obtaining data on new locations of little-known rust fungi.Key words: Trans-Ili Alatau, Ile-Alatau national park, location, host-plant, rust fungus, teliostage, urediniostage, aeciostage.